2016
DOI: 10.1590/1809-98232016019.140232
|View full text |Cite
|
Sign up to set email alerts
|

Transição entre níveis de fragilidade em idosos no município de Belo Horizonte, Minas Gerais

Abstract: Objective: To observe possible changes in frailty phenotype classification over time. Method: 40 individuals of both genders aged over 65 years, living in the metropolitan region of Belo Horizonte, Minas Gerais and identified in a base line Rede FIBRA assessment as frail, who could walk independently or with the aid of devices and who had no illnesses that would prevent tests being carried out, , were considered. A standardized survey previously established by Rede FIBRA was administered. Results: The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
5
1
1
Order By: Relevance
“…Most of our subjects had a constant frailty state (58%). However, frailty state improvement in our study was lower than Faria et al’s (14.8% vs 45%) [26]. Nevertheless, it showed that there is a possibility for individuals to transition into lesser frailty states, although the probability is low.…”
Section: Discussioncontrasting
confidence: 86%
“…Most of our subjects had a constant frailty state (58%). However, frailty state improvement in our study was lower than Faria et al’s (14.8% vs 45%) [26]. Nevertheless, it showed that there is a possibility for individuals to transition into lesser frailty states, although the probability is low.…”
Section: Discussioncontrasting
confidence: 86%
“…Some longitudinal studies reported on the ability of older community-dwelling adults to move between frail states, suggesting that individuals previously classified as frail and pre-frail, according to the frailty phenotype, may have a reduction in the number of positive criteria scored over time (Faria et al, 2016;Ye et al, 2020). This issue reaffirms the dynamic and reversible character of frailty (Lopez et al, 2018); thus, we emphasize the importance of health strategies that can optimize this state transition, establish appropriate therapies to minimize or reverse frailty, and benefit from clinical decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that sarcopenia is one of the components of the frailty tripod, combined with neuroendocrine dysfunction and immune system dysregulation (Faria et al, 2016;Silva et al, 2016), its results can be improved with exercise interventions in older adults (Lopez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Como 54 idosos faleceram e é possível que estes apresentassem os piores níveis de fragilidade, talvez isso explique essa suposta melhora. É possível uma melhora espontânea da fragilidade, uma reversão de níveis ruins e até reabilitação do idoso considerado frágil, neste caso são necessárias intervenções assistenciais 21 . Outra ação positiva que pode colaborar para melhora dos níveis de fragilidade é a educação em saúde.…”
Section: Discussionunclassified